A STUDY ON THE STUDENTS LISTENING SKILLS AT THE FIRST SEMESTER OF ENGLISH STUDY PROGRAM ISLAMIC UNIVERSITY OF INDRAGIRI - M. Arjun; Agus Mustajib; Maizarah (Program Studi Pendidikan Bahasa Inggris, 2025)
In the era of globalization, English plays a key role in many areas, including economics, politics, culture, communication, and education. Therefore, in response to this, English is very important to be mastered in Indonesia. The ability to listen to dialogue is one of the important language skills to be mastered by students. The ability to listen to student dialogue in Indonesia is still relatively low. The purpose of this study was to know student’s ability on listening to dialogue at the first semester in Islamic University on Indragiri. The sample of this study semester 1 English Study program, it means there are 22 students in round 5 male and 17 female. Sampling was carried out using purpose sampling. This study used a qualitative descriptive. Based on the results of the study the mean score of 61.37 categorizes most students as